Numeracy Literacy Skills of Elementary School Students through Ethnomathematics-Based Problem Solving - Iswara, Harum Sunya; Ahmadi, Farid; Ary, Deasylina Da (International Journal Labs, 2022)
Background: Numeracy literacy is one of the aspects evaluated in the Minimum Competency Assessment (AKM), referring to the Programme for International Student Assessment (PISA) as a good practice for international level assessment. Aim: This study aims to analyze the numeracy literacy ability of elementary school students in ethnomathematics-based problem solving. Method: This research is a qualitative descriptive research with a case study method taking the subject of 28 grade IV students of SDN Lamper Kidul 02. Data collection techniques in this study used tests and interviews. The results showed that students' numeracy literacy skills in level 1 questions were categorized as high, numeracy literacy for level 2 and level 3 questions was categorized as moderate. Findings: Students' numeracy literacy ability is classified as being in ethnomathematics-based mathematical problem solving, especially in the aspect of understanding problems as the key to problem solving skills, so that students have difficulty in planning settlement strategies, implementing solutions and re-examining results based on existing problem solving stages, this is triggered by students' lack of skill in numeracy and lack of maturity of mathematical concepts student-owned. Indirectly, numeracy literacy skills in problem solving based on ethnomathematics can affect numeracy skills, the maturity of mathematical concepts which is the main factor triggering students' anxiety about mathematics lessons.